Analisis Efisiensi Aktivitas Marketing: Assessment Ocean, Kinerja Pegawai Toyota Surabaya - Wira Kumara Cittopacama, Bima; Hanoum, Syarifa (Fakultas Ekonomi Universitas Gresik, 2023)
This research will examine the relationship between employee personality traits based on the OCEAN assessment that influence job performance during marketing activities. The approach used in this study is a survey with Likert scale. The population and sample were obtained using probability sampling. Based on the research title,